Equine odontoclastic tooth resorption and hypercementosis: Investigating individual incisor disease patterns using radiological classification. (13th July 2022) - Rehrl, Sabine; Schulte, Wiebke; Staszyk, Carsten; Lischer, Christoph
Abstract: Background: Equine odontoclastic tooth resorption and hypercementosis (EOTRH) is a destructive, painful and underdiagnosed dental disorder. Radiography is necessary to fully assess the disease as early stages occur on clinically normal teeth. Objectives: To investigate the distribution pattern of appearance of EOTRH within the incisor arcade. In particular, we aimed to determine the influence of tooth position and horse age on the severity of EOTRH as well as on the frequency of the individual severity stages. Study design: Retrospective cross‐sectional radiographic case study. Methods: Digital radiographs of 142 horses (10 years and older) presented for routine dental examination at our Equine Hospital were obtained and evaluated for changes related to EOTRH. Radiological findings were classified in terms of EOTRH severity, and each tooth was evaluated individually (tooth stage). Results: The tooth stages of EOTRH showed a bilateral symmetrical distribution pattern over the entire incisor arcade. There was a significant positive correlation between age and tooth stages ( p  < 0.001, rho = 0.48, 95% CI 0.43–0.51), and the frequency of higher tooth stages increased from central incisors to middle and corner incisors. Main limitations: Individual head anatomy in some male horses lead to superimposition of the lower jaw corner incisors and canine teeth. The radiographic technique proved difficult in smaller and uncooperative horses. Differentiating between mild pathological signs of EOTRH and age‐related radiological changes was not possible in all cases. Conclusion: These results reconfirm an age‐correlated progression of EOTRH. EOTRH affects the incisor arcade in a bilaterally symmetrical pattern with the corner incisors being the most severely affected. Zusammenfassung: Hintergrund: Odontoklastische Zahnresorption und Hyperzementose bei Pferden (EOTRH) ist eine destruktive, schmerzhafte und unterdiagnostizierte Zahnerkrankung. Zur vollständigen Beurteilung der Krankheit ist eine Röntgenuntersuchung erforderlich, da frühe Stadien bereits an klinisch normalen Zähnen auftreten. Ziele: Das Ziel dieser Studie war es, das Verteilungsmuster des Auftretens von EOTRH innerhalb der Schneidezahnarkade zu untersuchen. Insbesondere wollten wir den Einfluss der Zahnposition und des Pferdealters auf den Schweregrad von EOTRH, sowie auf die Häufigkeit der individellen Schweregrade bestimmen. Studiendesign: Retrospektive radiologische Querschnittsstudie. Methoden: Von 142 Pferden (10 Jahre und älter), die in unserer Pferdeklinik zur Routineuntersuchung vorgestellt wurden, wurden digitale Röntgenbilder angefertigt und auf Veränderungen im Zusammenhang mit EOTRH ausgewertet. Die radiologischen Befunde wurden nach dem Schweregrad der EOTRH klassifiziert, wobei jeder Zahn einzeln bewertet wurde (Zahnstadium). Ergebnisse: Die Zahnstadien von EOTRH zeigten ein bilateral‐symmetrisches Verteilungsmuster über die gesamte Schneidezahnarkade. Es bestand eine signifikante positive Korrelation zwischen dem Alter und den Zahnstadien ( p  < 0, 001, rho = 0, 48, 95% CI 0.43–0.51), und die Häufigkeit höherer Zahnstadien nahm von den zentralen Schneidezähnen zu den mittleren und Eckschneidezähnen zu. Hauptlimitationen: Die individuelle Kopfanatomie mancher männlichen Pferde führte zu einer Überlagerung der Unterkiefer‐Eckschneidezähne und der Hängstzähne. Die Röntgentechnik erwies sich bei kleineren und unkooperativen Pferden als schwierig. Die Unterscheidung zwischen leichten pathologischen Anzeichen von EOTRH und altersbedingten radiologischen Veränderungen war nicht in allen Fällen möglich. Schlussfolgerungen: Die Ergebnisse unserer Studie bestätigen eine alterskorrelierte Verschlechterung von EOTRH. Darüber hinaus beeinträchtigt EOTRH die Schneidezahnarkade in einem bilateral‐symmetrischen Muster, wobei die Eckschneidezähne am stärksten betroffen sind.